Tapered Bladed of Vertical Axis Wind Turbine for Powering Street Lights in Urban Areas in Indonesia with Wind Speed of 2-4 m/s - Maria Fransisca Soetanto ,; Astor , Yackob; Wibowo , Singgih Satrio; Syaiful ,; Zuhri , Muhammad Rizki; Luthfi , Mochammad (International Journal of Integrated Engineering, 2024)
This paper presents the development of a vertical axis wind turbine  (VAWT) with blades in the form of a taper curved profile using caps on the top and bottom of the turbine. The blade development was carried out based on numerical calculations using the Computational Fluid Dynamic (CFD) method using ANSYS Workbench 2018 software by comparing the use of conventional blades. The flow pattern that occurs around the turbine shows that the tapered curved blade design has a more distributed vortex formation pattern compared to conventional curved blades, and the turbulence that occurs at tip speed ratio, or TSR = 1.0 is still in the turbine blade area, which means the wind turbine in this research has a larger speed range compared to previous research. The experimental results of the characteristics of the wind turbine prototype parameters obtained the maximum coefficient of power, Cp-max = 0,14  at TSR 1.11, and was able to turn on LED street light and was able to fully charge the battery within 4 hours. The experiment results of this study are presented in the form of bar chart of Cp-max, compared with the Savonius results of previous studies, at almost the same TSR. It is obtained that the Cp of this wind turbine works with Cp 18.9 % greater than the previous results. So this wind turbine is suitable for use in urban areas in Indonesia which have wind speeds of 2 – 4 m/s.